The Effect of Job Stress and Cyberloafing on Organizational Commitment on Soe Bank Employees in The City of Surabaya - Sahrul Fahad; Anang Kistyanto (Ilomata International Journal of Management, 2021)
This research was conducted on employees of conventional state owned banks in the city of Surabaya. The goals of the research to analyze the relationship beetween job stress and cyberloafing on organizational commitment. Data collection used interviews and online questionnaires. The questionnaire consisted of 26 questions and was filled in by 58 respondents. Testing instruments using validity and reliability tests. The classical assumption test used on the research which included linearity test, heteroscedasticity test, multicollinearity test, and normality test. Regression test using multiple linear regression analysis. Testing hypothesis using the t test. research results reveal that job stress has no effect on organizational commitment, but the results of cyberloafing found that there was a positive effect on organizational commitment.